CSR DAN LEVERAGE: PERAN MODERASI DARI INVESTOR ATTENTION DAN STOCK LIQUIDITY - Safira Nur Izzaty; Agung Juliarto (Diponegoro Journal of Accounting, 2026)
This study examines the effect of Corporate Social Responsibility (CSR) performance on corporate leverage and the moderating role of investor attention and stock liquidity in non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Using secondary data from annual reports and ESG scores obtained from Bloomberg, this research applies purposive sampling and obtains 270 observations. Leverage is measured by the debt to asset ratio, CSR performance is measured using ESG scores, investor attention is proxied by institutional ownership, and stock liquidity is measured by turnover volume. The data are analyzed using multiple linear regression and moderated regression analysis. The results show that CSR has a positive and significant effect on corporate leverage, indicating that companies with higher CSR performance tend to have higher leverage levels, although this finding is not consistent with the proposed hypothesis. In addition, investor attention and stock liquidity are unable to moderate the relationship between CSR and leverage, suggesting that higher investor attention and stock trading activity do not directly influence the relationship between CSR performance and corporate capital structure decisions.